Need makes good schoolers": Spender and the Poverty of Aesthetics - Dodson, Joel M. (Political Aesthetics in the Era of Shakespeare, 2020)
Keywords: dept.eng

Incision - Furey, Rachel (Flyaway: Journal of Writing & Environment, 2020)
Keywords: dept.eng; literary-work

A History of Lace; The Great Chain of Being - Sonnenschein, Dana (Feminist Studies, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

Edgerton Park (Poem) - Sonnenschein, Dana (Hobo Camp Review, 2020)
Keywords: dept.eng

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
tex.ids: sinclairBecomingAlliesAccomplices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084794698 type: Article
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Mary Johnson of Wethersfield, Connecticut, hanged for witchcraft, 1648 (poem) - Shipley, Vivian (Connecticut Literary Anthology: Celebrating Nutmeg Authors, 2020, 2020)
Connecticut Literary Anthology features thirty-six Connecticut poets and prose writers from across the Nutmeg State. The 2020 Anthology is published by the Central Connecticut State University English Department. The writers in the inaugural anthology share themes amplified by current events, but not the context. Stories of family, economic in- equality, sexual violence, social justice, culture wars, lost love, aging, and gender—they’re all in here. And mangoes. Everyone loves mangoes. Featured writers: Janet L. Bannister, Charles V. Belson, Susan Cinoman, Ginny Lowe Connors, Jason Courtmanche, Catherine DeNunzio, Joanie DiMartino, Catherine DeNunzio, Meghan Evans, Maura Faulise, Kathryn Fitzpatrick, Beth Gibbs, Cecilia Gigliotti, Nichole Gleisner, Sitara Gnanaguru, Emi Gonzalez, José B. González, Benjamin S. Grossberg, Avery Jenkins, B. Fulton Jennes, Sarah Darer Littman, Kiran Masroor, Melissa McEwen, Claudia McGhee, Nancy McMillan, Jean P. Moore, Steven Ostrowski, Makenzie Ozycz, Aimee Pozorski, Kara Molway Russell, Vivian Shipley, Amy Sisson, Katherine A. Szpekman, Wendy Terry, Mika Taylor, Marina Tinone, Jason Wilkins. Praise for Anthology: "It feels like we have become unglued from one another since March of 2020; masked strangers passing each other in anonymity. But this anthology glues us back together and helps us find ways to heal and talk with one another. Important stories are told, and we should heed them." —Lisa Comstock, Director for Connecticut Center for the Book
Keywords: dept.eng

Maps for Jackie - Labbe, Jason (BlazeVOX Books, 2020)
"Poetry's natural habitat is one of detail, radiant or tarnished, an intimate geography that draws us close to where presence is an act of perception: world into word. In Maps for Jackie, Jason Labbe navigates a terrain of singular encounters and incidents, tactile, luminous and animated by the sensuous abrasions and comforts of the heartmind as they touch down on his, and our, present: white leaf is like a moth / wing I'd fix to her shoulder.–Ann Lauterbach"–The back cover
Keywords: 21st century; American poetry; dept.eng; faculty_collection

Michelangelo's Captive - Sonnenschein, Dana (The Ekphrastic Review, 2020)
Michangelo’s Captive ​ I wished to photograph a beautiful man sculpted by Michelangelo, afraid I would forget him if I did not, for he had no story, no name. But I turned away. I had the...
Keywords: dept.eng; ⛔ No DOI found

Utility, artistry, and narrative control in Herman Melville's "The Bell-Tower" - Ellis, Scott (College Literature, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

"Train & Pool," “The Colonel Takes a Position," "Summer Almanac," "Cloud Study," "Light, A Reagent," Author's Statement: "Writing, For and To" - Johnson, Brian (Parhelion, 2020)
Keywords: dept.eng; ⛔ No DOI found

"Asides" and "Household" - Johnson, Brian (Court Green, 2020)
Keywords: dept.eng; ⛔ No DOI found

Maple Street, London (1915) - Johnson, Brian (The Ekphrastic Review, 2020)
Keywords: dept.eng; ⛔ No DOI found

Rhubarb Leaf - Johnson, Brian (great weather for MEDIA, 2020)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Tour - Johnson, Brian (The Main Street Rag, 2020)
Keywords: dept.eng; ⛔ No DOI found

W. D. Howells, William James, and the pragmatist pluralism of “The Angel of the Lord” - Petrie, Paul (American Literary Realism, 2020)
0 citations (Crossref) [2023-10-31] tex.ids: petrieHowellsWilliamJames2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091388735 type: Review
Keywords: dept.eng

Interpreting blake’s the magdalene at the sepulchre - Rosso, GA (Blake/An Illustrated Quarterly, 2020)
tex.ids: rossoNowMyEyeinpress
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Gender, genre, and lesbian identity in four modernist Jewish texts - Blackmer, Corinne E. (Teaching Options in Jewish American Literature, 2020)
Keywords: dept.eng

Unsettling transcription through “event memory”: problem and possibility in exploring the phenomenological question - Sinclair, Meredith N. (Qualitative Inquiry, 2020)
This article works to unsettle the use of transcription in qualitative inquiry by troubling the truth claims of transcribed text. Building on the hermeneutic phenomenology of Van Manen, it explores the way the researcher might “write through” transcribed text to return to the two-dimensional text space a more honest reading of lived experience. It also draws on Deleuze and Guattari’s rhizomatic thinking to explore the “gruesome multiplicities” present in reality—and the ways we might honor that multiplicity in research texts. Excerpts from an inquiry into the phenomenon of “reading as not a reader” are used to illustrate.
1 citations (Crossref) [2023-10-31] tex.ids: lens.org/070-679-779-525-700, pop00318, sinclairUnsettlingTranscriptionEvent2018, sinclairUnsettlingTranscriptionEvent2018a, sinclairUnsettlingTranscriptionEvent2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85059284090 tex.type: [object Object] type: Article
Keywords: dept.eng; hermeneutic phenomenology; methodologies; methods of inquiry; peer-reviewed; qualitative research; qualitative research and education; transcription; writing as method of inquiry